Novice university educators: professional, psychological and motivational spheres of adaptation. Issue 1 (September 2020) - Karpovich, I. A.; Krepkaia, T. N.; Voronova, L. S.; Combarros-Fuertes, P.
Abstract: The article is focused on the issue of adaptation of novice university teachers. The purpose of this study is: 1. to assess the professional readiness of the novice university educators; 2. to find out the problems they face in professional, psychological and motivational spheres; 3. to compare the frequency of the detected problems within the groups of novice teachers with 1-3 year and 3-5 year experience. The article presents the results of a study conducted among novice educators (N 40) at Peter the Great St. Petersburg Polytechnic University. Results made it possible to figure out the main problems teachers face in professional, psychological and motivational spheres of induction process. Comparison of novice teachers (1-3 year experience) and young teachers (3-5 year experience) resulted in the findings that although there is a positive tendency in all the spheres of adaptation, the difference between the values of novice and young teachers is in most cases statistically insignificant. It makes it possible to conclude that university educator with experience of about 5 years still need support that can be provided by mentoring and individual assistance, performed in the form of on-the-job training, instructional interactions with mentors and experienced colleagues.